Percutaneous Coronary Intervention on Saphenous Vein Graft in Second Generation Drug Eluting Stent Era - Milenko Čanković; Andrej Preveden; Vladimir Ivanović; Aleksandra Milovančev; Milovan Petrović; Mila Kovačević; Tatjana Miljković; Marija Bjelobrk; Lazar Velicki (Acta Clinica Croatica)
The aim of the study was to determine major adverse cardiac events (MACE) related to the percutaneous coronary intervention (PCI) on saphenous vein graft (SVG) with a second- generation drug eluting stents in patients with previous coronary artery bypass graft (CABG). The research was conducted as a unicenter retrospective observational study which analyzed consecutive patients of both genders who had PCI on SVG from January 1, 2016 until June 30, 2019. The aim was to investigate the occurrence of MACE defined as development of periprocedural myocardial infarction, acute heart failure in the first 24 hours after PCI, unstable angina after PCI, periprocedural stroke, contrast induced nephropathy, death, acute/subacute/late stent thrombosis, and target lesion revascularization. The study included 97 consecutive patients. MACE was recorded in 20.6% of patients, more often in patients with thrombolysis in myocardial infarction grade flow ≤2. High thrombus burden (HTB) was detected in 44.3% of patients and it significantly contributed to the development of MACE. In conclusion, PCI on SVG is a highly challenging procedure, especially in patients with an acute coronary syndrome. In patients who have HTB recorded in SVG, the usage of thrombus aspiration and distal protection device can reduce the frequency of no-reflow phenomenon and consequential MACE.